Physical activity, sedentary behaviour, and childhood asthma: a European collaborative analysis - Eijkemans M; Mommers M; Harskamp-van Ginkel MW; Vrijkotte TGM; Ludvigsson J; Faresjö Å; Bergström A; Ekström S; Grote V; Koletzko B; Bønnelykke K; Eliasen AU; et al. (BMJ Publishing Group, 2025)
Objectives
To investigate the associations of physical activity (PA) and sedentary behaviour in early childhood with asthma and reduced lung function in later childhood within a large collaborative study.
Design
Pooling of longitudinal data from collaborating birth cohorts using meta-analysis of separate cohort-specific estimates and analysis of individual participant data of all cohorts combined.
Setting
Children aged 0-18 years from 26 European birth cohorts.
Participants
136 071 individual children from 26 cohorts, with information on PA and/or sedentary behaviour in early childhood and asthma assessment in later childhood.
Main outcome measure
Questionnaire-based current asthma and lung function measured by spirometry (forced expiratory volume in 1 s (FEV1), FEV1/forced vital capacity) at age 6-18 years.
Results
Questionnaire-based and accelerometry-based PA and sedentary behaviour at age 3-5 years was not associated with asthma at age 6-18 years (PA in hours/day adjusted OR 1.01, 95% CI 0.98 to 1.04; sedentary behaviour in hours/day adjusted OR 1.03, 95% CI 0.99 to 1.07). PA was not associated with lung function at any age. Analyses of sedentary behaviour and lung function showed inconsistent results.
Conclusions
Reduced PA and increased sedentary behaviour before 6 years of age were not associated with the presence of asthma later in childhood.